Expanding Diversity to More Fully Include Those Disabled/Differently Abled in Social Work Practice; Issues of Relatedness, Social Justice, Inclusiveness and Diversity among Social Work Colleagues, in the Clinical Dyad and the Community-at-Large. - Chalfin, Fanny (Psychoanalytic Social Work)
This paper will discuss disability as a neglected aspect of cultural competency in the diversity literature and among social work colleagues. It identifies some of the unconscious intrapsychic and sociocultural concepts that contribute to the avoidance of and malaise around people with disabilities in the community at large as well as in the social work community. Personal and cultural aspects of unanalyzed countertransference and transference are examined. The impact of those internalized sociocultural concepts and projections among colleagues will also be explored. Through anecdote, parallel processing, and the literature, it will be shown how some of the transference issues toward the disabled clinician can become assets in the therapeutic alliance, and how colleagues can become more at ease with differently abled peers particularly through the use of an embodied sense of compassion, greater self-awareness and wisdom.